2010
DOI: 10.1681/asn.2009121306
|View full text |Cite
|
Sign up to set email alerts
|

Renal Actions of RGS2 Control Blood Pressure

Abstract: The role of G protein-coupled receptors (GPCRs) in hypertension and cardiovascular diseases is well established. 1 Moreover, pharmacologic antagonists of GPCRs, such as ␤-adrenergic and angiotensin receptors, are cornerstones of therapy in the treatment of hypertension and its complications. 2 Signaling by GPCRs is triggered by ligand-induced conformational changes in the receptor that promote exchange of guanosine 5Ј-diphosphate for guanosine 5Ј-triphosphate on the G␣ subunit of the G protein complex, 3 follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…RGS2 protein levels were also increased in the kidney (Fig. 6B), where RGS2 has been proposed to exert effects on blood pressure homeostasis (Gurley et al, 2010).…”
Section: Rgs2 Protein Was Stabilized By Ctssmentioning
confidence: 87%
“…RGS2 protein levels were also increased in the kidney (Fig. 6B), where RGS2 has been proposed to exert effects on blood pressure homeostasis (Gurley et al, 2010).…”
Section: Rgs2 Protein Was Stabilized By Ctssmentioning
confidence: 87%
“…These studies have identified single nucleotide polymorphisms within the coding region of RGS2 that result in a decrease of proper localization of RGS2 to the plasma membrane and a resultant decrease of its inhibitory influence on G␣ qmediated vasoconstrictive hormone signal transduction (Yang et al, 2005;Gu et al, 2008). Promoter polymorphisms in the RGS2 gene locus and renal actions of RGS2 have also been highlighted as contributing factors to the intrinsic homeostatic and extrinsic therapeutic control of blood pressure maintenance (Gurley et al, 2010;Semplicini et al, 2010;Sugimoto et al, 2010). In addition, the RGS2-deficient mouse was instrumental in demonstrating the role for RGS2 protein action in cardiac compensation to blood pressure overload and the antihypertrophic effects of PDE5 inhibition (Takimoto et al, 2009).…”
Section: Regulators Of G-protein Signaling 2 4 5 and 6 In Cardimentioning
confidence: 99%
“…Mice lacking RGS2 develop hypertension for unknown reasons. 8 Gurley et al 7 now show that transplanting kidneys from hypertensive RGS2 Ϫ/Ϫ mice increases BP in wildtype mice, demonstrating the dominant effect of the kidneys for this gene.…”
mentioning
confidence: 94%
“…In this issue of JASN, Gurley et al 7 use the cross-transplantation method to study the role of the regulator of G protein signaling type 2 (RGS2) that is implicated in hypertension. There is growing evidence that G proteincoupled receptor (GPCR)-mediated control of vascular tone and BP is an important regulatory step in the development of hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation